(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
Gold-bearing of Sevan–Amassiya zone is more or less studied in its central part along the zone of large fault near latitude of strike. Rather perspective is the southern flank of tectonic zone, where in the contact parts of the terrigenous-carbonaceous facieses of the Upper Cretaceous with the volcanogenous-sedimentary rocks of the Eocene and Miocene thick zones with gold content up to 2.0–2.5 g/t are revealed. Practical interest is represented also to the scatterings of the area, where Sotk and Dilidjan deposits are located.